2014
DOI: 10.1051/0004-6361/201323041
|View full text |Cite
|
Sign up to set email alerts
|

The Earth as an extrasolar transiting planet

Abstract: Context. The atmospheric composition of transiting exoplanets can be characterized during transit by spectroscopy. Detections of several chemical species have previously been reported in the atmosphere of gaseous giant exoplanets. For the transit of an Earth twin, models predict that biogenic oxygen (O 2 ) and ozone (O 3 ) atmospheric gases should be detectable, as well as water vapour (H 2 O), a molecule linked to habitability as we know it on Earth. Aims. The aim is to measure the Earth radius versus wavelen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
(79 reference statements)
1
27
1
Order By: Relevance
“…2.2. Arnold et al (2014) observed the 21 December 2010 lunar eclipse with two high-resolution ESO spectrographs: HARPS and UVES. They applied a similar method as V10 and obtained the high-resolution transmission spectrum from the penumbral spectrum.…”
Section: Ca II and Na I Features In Lunar Eclipse Observationsmentioning
confidence: 99%
“…2.2. Arnold et al (2014) observed the 21 December 2010 lunar eclipse with two high-resolution ESO spectrographs: HARPS and UVES. They applied a similar method as V10 and obtained the high-resolution transmission spectrum from the penumbral spectrum.…”
Section: Ca II and Na I Features In Lunar Eclipse Observationsmentioning
confidence: 99%
“…We found that the CLV effect in solar lines results in large residuals in the transmission spectrum obtained and that the CLV effect can lead to the false detection of atmospheric species. For example, the detection of Na i was claimed in some other lunar eclipse observations (Pallé et al 2009;Vidal-Madjar et al 2010;Arnold et al 2014), but was demonstrated to be the result of the CLV effect rather than of actual planetary absorption.…”
Section: Introductionmentioning
confidence: 98%
“…Visible or near IR Earthshine spectra have been analysed by, e.g., Woolf et al [22], Pallé et al [23], García Muñoz et al [24]. Water vapor and biogenic oxygen and ozone have been identified in high resolution Vis-NIR transmission spectra of Earth seen during the December 2010 Moon eclipse by Arnold et al [25]. EPOXI (Extrasolar Planet Observation and Characterization -Deep Impact eXtended Investigation) observations of Earth have been used by Rugheimer et al [19], Kaltenegger et al [26], Robinson et al [27] for radiative transfer code validation.…”
Section: Introductionmentioning
confidence: 99%